Implementation Strategy of Tri Hita Karana in the Family toward a Healthy Community - Ni Wayan Rasmini (Universitas Pendidikan Ganesha, 2022)
Tri Hita Karana is the life values of the Balinese Hindu culture community, including palemahan, pawongan, and parahyangan, which are integrated and holistic in self, family, and society. However, the application of Tri Hita Karana in the school environment and early childhood learning is still relatively low. This study aims to formulate a strategy for implementing the Tri Hita Karana philosophy within the family toward a healthy society. This type of research is qualitative. The research subjects were 125 people. Observation, interviews, and document studies carried out data collection. The credibility of the data was tested by applying the triangulation method and extending the observation time. Data analysis starts with data presentation, reduction, and conclusion/verification. The results of the data analysis are the strategy for implementing Tri Hita Karana starting from the pattern of thinking palemahan, pawongan, parahyangan and ways of thinking concrete, semi-concrete and abstract. The inculcation of values begins from the Banjar leaders and administrators, heads of families, and their members, which has implications for improving the health of individuals, families, and communities. Tri Hita Karana values must be implemented holistically and integratively to enhance health quality.